Where Love Meets Resilience: Lived Experience of Individuals with PWD Partner - Jasmine Malijan; Nicole Maniaga; Janille Malacaman; Shaina Mae Magsino; John Kierby Maniaga; Bea Zharina Pascual (Advanced Qualitative Research, 2026)
Romantic relationships involving a partner with a disability (PWD) present unique relational dynamics, including role shifts, communication barriers, financial strain, and social stigma, which test emotional resilience and family cohesion in the Philippine context. Grounded in Person-Centered Theory and the Social Model of Disability, this study examined the lived experiences of individuals with PWD partners, guided by the central question: “What are the lived experiences of individuals with a PWD partner?” and corollary questions on relational descriptions, identified themes, and recommendations.  Employing Interpretative Phenomenological Analysis (IPA), researchers purposely selected five participants aged 18–60 from Sto. Tomas and Tanauan City, Batangas, each with at least five years in a relationship with a PWD partner (stroke, deaf, dialysis, blind). Following Coker's (2021) guidelines for phenomenological saturation, semi-structured interviews were analyzed using QDA Miner Lite, yielding five major themes: (1) Family Strength, (2) Resilience, (3) Adaptation, (4) Mutual Family Solidarity, and (5) Perseverance. Subthemes included thoughtful care, communication issues, financial burden, determination, recovery, and shared responsibilities. Narratives highlighted adaptive communication, mutual support, and role flexibility as key to sustaining relationships despite challenges like misunderstandings, external shock, and emotional exhaustion.  Findings underscore that family and social support, empathy, and perseverance mitigate disability-related stressors, fostering relational stability amid societal stigma and economic hardship. The study emphasizes the need for enhanced government programs, counseling, and communication training to empower these families.